A new method to assess lumbar vertebral body rotation on simple radiographs - Suk-Joong Lee; Sanghyun Joung; Sungmin Kim; Hyun-Joo Lee; Maria Florencia Deslivia (Journal of Craniovertebral Junction and Spine, 2024)
Introduction and Objectives: A number of sophisticated methods have been used to identify the degree of vertebral rotation. This is an experimental model using saw bone and motorized device to identify the possible parameter of vertebral body axial rotation on simple radiographs. Materials and Methods: A sawbones model of the lumbar spine was used in this study. The sawbones was attached to a zigzag motorized rotation device. The device rotated the model vertebra by 1°. Fluoroscopic images were obtained for each pose. We developed a customized program to calculate the indices automatically. Three formulas were used to determine the ratio that corresponds to the rotation angle: (1) ratio of the total width of the vertebral body to the length between the lateral margin and center of two pedicles, (2) ratio of the total width of the vertebral body to the length between two pedicles, and (3) ratio of the length between two pedicles to the total width of the vertebral body. Results: The correlation coefficient between the rotation angle and formula 1 was −0.9995. The correlation coefficient for the other two parameters was extremely low (0.036 for formula 2 and 0.16 for formula 3). Conclusions: The rotation angle can be easily and accurately determined by calculating the abovementioned parameters on simple radiographs.